2011
DOI: 10.1016/j.jvs.2011.07.004
|View full text |Cite|
|
Sign up to set email alerts
|

Updated Society for Vascular Surgery guidelines for management of extracranial carotid disease: Executive summary

Abstract: In 2008, the Society for Vascular Surgery published guidelines for the treatment of carotid bifurcation stenosis. Since that time, a number of prospective randomized trials have been completed and have shed additional light on the best treatment of extracranial carotid disease. This has prompted the Society for Vascular Surgery to form a committee to update and expand guidelines in this area. The review was done using the GRADE methodology.[corrected] The perioperative risk of stroke and death in asymptomatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
179
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(184 citation statements)
references
References 0 publications
1
179
0
4
Order By: Relevance
“…Based on studies reporting an upfront surgical complication rate ranging from 2.3% 33 to 3.1% 34 among patients undergoing CEA for asymptomatic stenosis of .60%, and an absolute risk reduction for stroke or death of roughly 5% to 6% in the surgical group at 5 years, several medical specialty societies [35][36][37][38] have recommended that surgery for asymptomatic patients be reserved for those with a perioperative complication risk of ,3% and a life expectancy of greater than 3 to 5 years. Although recent studies have reported lower stroke rates with improvements in both surgical 36 and medical management, 39 no recent randomized trials have compared these treatments.…”
Section: Don't Perform Emgs For Back Pain Without Symptoms or Signs Omentioning
confidence: 99%
“…Based on studies reporting an upfront surgical complication rate ranging from 2.3% 33 to 3.1% 34 among patients undergoing CEA for asymptomatic stenosis of .60%, and an absolute risk reduction for stroke or death of roughly 5% to 6% in the surgical group at 5 years, several medical specialty societies [35][36][37][38] have recommended that surgery for asymptomatic patients be reserved for those with a perioperative complication risk of ,3% and a life expectancy of greater than 3 to 5 years. Although recent studies have reported lower stroke rates with improvements in both surgical 36 and medical management, 39 no recent randomized trials have compared these treatments.…”
Section: Don't Perform Emgs For Back Pain Without Symptoms or Signs Omentioning
confidence: 99%
“…Two guidelines 41,46,47 cited the Stenting and Angioplasty With Protection in Patients at High Risk for Endarterectomy Trial (SAPPHIRE) 79 for defining high-CEA-risk clinical scenarios. Twenty-nine guidelines included specific recommendations for the use of CAS for patients with high-CEA-risk ACS 28,31,32,[35][36][37][38]41,[43][44][45][46][47][55][56][57][58]62,63 or SCS,27,28,[31][32][33][34][35][36][38][39][40][41][42][44][45][46][47][48][49][50][51][52][53][54][55][56]58,[61]…”
mentioning
confidence: 99%
“…[36][37][38][39]42,48,49,[54][55][56][57]62,63 In the other 17 guidelines, the cause of high-CEA-risk was characterized as being because of only reasons related to vascular anatomy and in others as being because of vascular anatomy or medical comorbidities. Nine of these guidelines gave no specific examples of high-CEArisk scenarios [42][43][44][45]48,49,54,57,63 or referred to other guidelines. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The document was long awaited, and was purposefully delayed until February 2011, in order to be able to consider the most recent data from the largest randomized clinical trial, Carotid Revascularization Endarterectomy versus Stenting Trial (CREST) [2]. In September 2011, the Society for Vascular Surgery (SVS), which had endorsed the broad-based multispecialty guideline in February 2011, published a contradictory guideline [3]. The SVS guideline reneged on the compromise recommendations made several months before, which had been endorsed by the SVS leadership.…”
mentioning
confidence: 99%